Hypertension, as an iceberg disease in the high hilly areas of Nepal - Lamsal, KS; Kafle, MP (Journal of Institute of Medicine Nepal, 2013)
Introduction: Hypertension simply is usual blood pressure of 140/90 mm Hg or higher in otherwise normal individuals and even lower for certain high-risk patients. Its a common medical condition worldwide. It is the most important, commonest and correctible cardiovascular risk factor and one of the leading causes of death. M any factors like dietary, behavioral, psychological, environmental, genetic etc have direct or indirect influence on hypertension. In this study we have analyzed the prevalence and different stages of hypertension in a remote and high hilly area of Nepal. Methods: The study was conducted in high hilly area adjoined to Solukhumbu and Dolakha districts. Altogether 600 participants were enrolled in the study. Participants having age more 18 years, regardless of symptoms, willing to give consent were involved. Demograghic data and blood pressure was recorded twice. The 1st reading was taken by trained nursing staff using standard Riva Rocci Sphygnomanometer after five minutes rest. The 2nd reading was taken by Physician and mean was calculated from both readings. Results: A mong 600 patients involved in the study, the mean age was 48 years. A mong them, 92 patients were having prehypertension including 53 male and 39 female. The stage I hypertension was found in 130 cases, out of them 77 were male and 53 were female. Whereas stage II hypertension was found in 84 cases, including 40 males and 44 females. Prehypertension was commonest among 40-49 years of age, stage I and stage II hypertension was commonest among 50-59 years. Systolic hypertension was more common in younger and elderly participants whereas diastolic hypertension was more common in middle age adults. Conclusion: In the study, the incidence of hypertension increases whose age was found between 50-59 with age till 50-59 years age group. Systolic hypertension was more common than diastolic hypertension in less than 30 years age group where as between 30-59 years diastolic blood pressure was more commonly found than systolic blood pressure. In the elderly of more than 60 years, again systolic hypertension is more predominant than diastolic hypertension. DOI: http://dx.doi.org/10.3126/joim.v34i3.8906 Journal of Institute of Medicine, December, 2012; 34:4-7